Prevalence of Thyrotropin Receptor Antibodies and Clinical Profile of Patients with Alopecia Areata: A Cross-Sectional Study - Stefanis, Athanasios J; Fialova, Alena; Arenberger, Petr (Skin appendage disorders, 2025)
INTRODUCTION: Alopecia areata (AA) is associated with thyroid dysfunction and abnormal levels of thyroglobulin and thyroid peroxidase autoantibodies. One study detected high prevalence of thyrotropin receptor antibodies (TRAbs) in AA patients. Our aim was to investigate the prevalence of TRAb levels in AA patients and to assess their association with thyroid hormones, other thyroid antibodies, AA severity, and other epidemiological variables. METHODS: In this observational study, 139 patients (97 females, 42 males), aged 12 and above, with newly presenting, relapsing, or treatment-resistant AA were included. Medical histories were reviewed, alopecia severity was assessed using the Severity of Alopecia Tool (SALT), and blood tests measured thyroid hormones and autoantibodies. RESULTS: The prevalence of TRAb was significantly higher in AA patients (23.6%) compared to the general population (1-2%) (p < 0.001). Elevated TRAb titers did not correlate with diagnosed thyroid dysfunction or treatment, abnormal thyroid function tests and autoantibodies, AA severity, duration, and onset. Male patients exhibited a significantly higher prevalence of abnormal TRAb titers compared to females (75.0% vs. 21.3%, p = 0.002). CONCLUSION: A significant proportion of AA patients presented with elevated TRAb levels, independent of thyroid hormone titers, other thyroid autoantibodies, or SALT score. Prevalence of abnormal TRAb levels was higher in males.